Research on nodal wind power values and optimal accommodation based on locational marginal price. (July 2019) - Jiang, Yuewen; Guo, Liyun; You, Shi
Highlights: Line transmission margin value considering wind power is assimilated into LMPs. Value of wind farms at each node is evaluated based on LMPs and power flow tracing. A model to optimize the accommodation and value for each wind farm is established. Critical impact of load on wind power accommodation of each wind farm is identified. Abstract: Under the current grid operation mode, reasonable integration of wind power is conducive to the exertion of its value. In this paper, the line flow transmission margin value considering wind power integration is assimilated into the locational marginal price (LMP). Accordingly, the LMP includes four components: energy consumption, network loss, congestion and line flow transmission margin. Based on the LMP difference of load nodes before and after wind power integration and the idea of power flow tracing, the specific values of different grid-connected wind farms at each node are evaluated, namely, the energy value and the network value of wind power. The load nodes that have a critical impact on wind power accommodation for each wind farm are identified. Moreover, the reserve cost caused by the uncertainty of wind power is considered, in which the maximum total value of all wind farms is set as the optimal objective. Finally, this paper analyses the LMP, value and accommodation of a single wind farm in detail through a microgrid system and an IEEE 118-bus system with multiple wind farms to verify the proposed method.